ESCALA PARA ESTIMATIVA DA CARGA DE TRABALHO DA ENFERMAGEM EM UNIDADES DE TERAPIA INTENSIVA - Camargo, Maryanni Magalhaes (2020)
Introduction: Nurses in their clinical practice in Intensive Care Units (ICU) use scales to assess clinical severity and nursing workload to direct care and adapt human and material resources to meet care demands. Thus, aiming to meet an institutional dem